Financial Performance Analysis of Regional Companies (Case Study on Regional Company “Rengganis” Probolinggo Regency, East Java 2018-2020) - Oktaviani, Nurlaili; Nasrifah, Maula (Tazkia Islamic University College, 2024)
The Rengganis Regional Company of Probolinggo Regency is a company engaged in services that manages (Sports Building) Sasana Krida Gymnasium & Tennis Court, Jabung Tirta Swimming Pool and Bremi Pesanggrahan. To determine the success of the company's ability to develop its business, we can assess the company's performance through financial reports. The purpose of this study was to determine the financial performance of the Rengganis Regional Company, Probolinggo Regency, East Java in 2018 - 2020 and to describe the financial soundness of the Rengganis Regional Company of Probolinggo Regency from 2018 to 2020 based on the Decree of the Minister of SK Menteri BUMN Nomor : KEP-100/ MBU/ 2002. The research approach that the author uses is a descriptive qualitative approach, which is directed at how the financial performance and health level of the Regional Company Rengganis Kab. Probolinggo. Data obtained from financial reports sourced from the Regional Company Rengganis Kab. Probolinggo in 2018, 2019 and 2020. The results show that the financial soundness of the Rengganis Regional Company during the three accounting periods, 2018, 2019 and 2020 according to the Decree of the Minister of SK Menteri BUMN Nomor : KEP-100/ MBU/ 2002 through 8 ratio indicators is not good. This is due to the less than optimal management of the financial performance of the Rengganis regional company.